Hemodynamics and Mitochondrial Energy Metabolism in Right Heart Hypertrophy after Acute Hypoxic Stress - Thürich, Thomas; Bereiter-Hahn, Jürgen; Schneider, Markward; Zimmer, Guido (Arzneimittelforschung, 1999)
Excessive right heart hypertrophy was investigated under additional acute hypoxic stress to find out a possible contribution of mitochondrial dysfunction to sudden heart failure. Severe right heart hypertrophy in rats was induced by exposure to hypobaric pressure (46 663 Pa) for 4 weeks. Heart rate, isovolumic pressure and coronary flow were determined in the Langendorff mode of perfusion. After normoxia, the hearts were subdued to acute hypoxia/reoxygenation. Mitochondrial membrane potential was measured at the heart surface by fluorometry using 2-(dimethylaminostyryl)- 1-ethylpyridinium iodide (DASPEI). At the end of each experiment mitochondria were isolated and ATP synthesis, ATPase, as well as creatine kinase activity were determined. Compared to normal hearts the heart rate is decreased in the hypertrophied group whereas right ventricular systolic and (end)diastolic pressure (adjusted to isovolumetric maxima) are increased. Coronary flow is decreased. Cytosolic creatine phosphate ATP levels and ATP/ADP ratios are significantly (p < 0.01) decreased. Furthermore, ATP synthesis and creatine kinase activities are diminished. At high ADP, respiration is loosely coupled or partially uncoupled. Acute hypoxia is particularly deleterious to hypertrophied hearts: Mitochondrial membrane potential as measured by heart surface fluorometry decreases extensively and is only very incompletely restored during reoxygenation. Rate-pressure product decreases precipitously and is restored during reoxygenation only to a very low extent. The results indicate an insufficient energy metabolism of mitochondria during acute hypoxia/reoxygenation which adds to the earlier described shifted isozyme pattern of myosin and decreased activities of myosin and sarcoreticular Ca 2+ ATPase, leading to myocardial failure in right heart hypertrophy.
Keywords: Cytosolic ATP/ADP ratio; Heart, experimental right heart hypertrophy, Langendorff perfused rat heart; Mitochondria, ATP synthesis, creatine kinase activity, energy status